The Slurry Wall: Past, Present, and Future. (31st August 2020) - Conte, Lisa; Graham-Felsen, Joe; Trienens, Amanda
ABSTRACT: One of the most telling artifacts in the 9/11 Memorial Museum is the slurry wall, a vestige in situ of the pre-9/11 World Trade Center complex, preserved under Section 106 of the National Historic Preservation Act. This subterranean 20 meter long section of the perimeter wall that surrounded 4.5 hectares of the Trade Center site was never meant to be seen or tell its story. Made of reinforced concrete, and tied back to bedrock, its job was to hold back the waters of the Hudson River. The wall was a marvel of engineering in its time and on 11 September 2001 withstood untold forces and thus acquired new meaning – the once mute, utilitarian object became a symbol of hope and resilience. The slurry wall no longer performs the work it was intended to – there is another loadbearing structure behind it – but remains in conversation with Mother Nature. The wall weeps, which has catalyzed corrosion of the steel, introduced salts and a host of other material concerns. The complexity of the slurry wall, as an artifact and an architectural element of the Museum that affects its environment, has necessitated collaboration between a diverse group of stakeholders to parse its secrets.